Israel : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Israel. (IMF Staff Country Reports; Country Report, 2021)
The economic impact of the COVID-19 pandemic is unprecedented. Israel's economic activity recorded a historic contraction, and the outlook remains challenging, with possible long-term scarring. Uncertainty is high, mainly driven by the evolution of the pandemic, the prospects for widespread vaccine distribution, and political uncertainty.